THE ROLE OF POLITICAL SCIENCE - Riak , Professor Gabriel Alier; Ayuel, Dut Bol (IJRDO - Journal of Social Science and Humanities Research, 2022)
Political science is the study of politics and its surrounding environment. This implies that the essence of political science is to open widely on the perspective of what goes round in the social order of any democratic state. There are considerable questions that emerge out of the political sphere to contend the manner in which politics is exhibited. These entails; what attitudes and values produce political conflicts and decent, what political organizations are active in the struggle to realize political maturity, what is the nature of socio-economic relationships inside a polity, how adequate are the resources to meet the needs of the society, hoe equitable are the resources distributed to suit the needs and the aspirations of the people, what are the constitutional structure and the decision making process of each nation and how well suited are they to that nations needs, what internal structures and procedures exist for the debate and resolution of the problems with that nation, why are some countries rich and developed in terms of democratic practices while others are not. These among other questions bets explain the relevance and undertaking enshrined in the study of political science.